Statement on additional scientific evidence in relation to the essential composition of total diet replacement for weight control - Castenmiller, Jacqueline (EFSA J, 2021)
Following a request from the European Commission, the EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA) was asked to revise the Opinion on the essential composition of total diet replacements for weight control (TDRs) regarding the minimum content of linoleic acid (LA) and alpha‐linolenic acid (ALA) and the maximum content of magnesium (Mg). Through a comprehensive literature search, human studies were retrieved reporting on LA and ALA concentrations in adipose tissue (AT), on weight loss and gallstone formation following TDR consumption and on diarrhoea after supplemental Mg intake. The distribution of the amount of LA and ALA release from AT during weight loss when consuming TDRs was estimated using statistical simulations. Using the fifth percentile, the coverage of the adequate intake (AI) for both FA was estimated. For the risk of developing diarrhoea when consuming TDRs with an Mg content of 350 mg/day, four cross‐over studies using 360–368 mg Mg/day were reviewed. The Panel concludes that (1) there is no need to add LA to TDRs, as the amount released from AT during weight loss when consuming TDRs is sufficient to cover the AI for LA; (2) a minimum of 0.8 g/day ALA is needed in TDRs in order to meet the AI for ALA; (3) the minimum fat content of TDRs of 20 g/day as derived in the Panel's previous opinion is proposed to be maintained until the availability of further evidence, given the considerable uncertainty as to the amount of fat required for reducing the risk of gallstone formation; and (4) the likelihood that Mg‐induced diarrhoea occurs at a severity that may be considered of concern for overweight and obese individuals consuming TDRs is low when the total maximum Mg content in TDRs is 350 mg/day.